Upaya mencegah kelebihan volume cairan Pada pasien chronic kidney diseaseDirsud dr.soehadi prijonegoro - Ratna Sari, Luzy, Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB (2016)
Bacground : The prevalence of chronic kidney disease is considered high in Indonesia, and this increase each year. Fluid volume excess which commonly appear as the complication of chronic kidney disease can affect the quality life of the patient. One kind of the symptoms which appear in the fluid volume excess is edema. Improper treatment of patient with chronic kidney disease can affect the sustainability of the patient. Therefore need prevention efforts to avoid fluid volume excess in appropriate treatment for chronic kidney disease. Objective : To describe the prevention efforts the fluid volume excess in patients with chronic kidney disease in the inpatient installation room of sakura at dr. Soehadi Prijonegoro Hospital. Methods : Method used is a descriptive method with a case study approach, conducted in the inpatient installation room of Sakura at dr. Soehadi Prijonegoro Sragen Hospital from the29th to 31st of March, 2016. The data was collected through observation, interviews with patients or relatives of patients, medical records, and further research. Results : The efforts done to prevent the fluid volume excess in the patients with chronic kidney disease is review of vital signs, such as inputs and outputs review, daily body weight check, limit the input of input and output, help to deal with discomfort feeling of fluid restriction, and collaboration in giving diuretics. The problem of fluid volume excesshas not been done, continue intervention. Conclusion : The fluid volume excess problem has not been covered, required for more effective fluid restriction treatment to reduce fluid volume excess, and it is expected to overcome the inconvenience feeling of fluid restriction by giving red guava juice.